Peluang dan Kesempatan Berwirausaha dari Sumber Daya Hayati (Tumbuhan) - Wawan Sujarwo (Universitas Sebelas Maret, 2025)
Ethnobiology is a field within biology that applies sustainable scientific principles to explore phenomena like ecology, social dynamics, and economics. Ethnobiology, in its application, predominantly uses plants for various purposes such as sustenance, traditional medicine, ceremonial materials, decorative plants, animal feed, and pest and weed management. Using ethnobotanical and pharmacological methods to preclinical and clinical investigations, this study intends to investigate the possibilities, particularly the use of plants, in creating business prospects derived from plant biodiversity. Data collecting involves examining database reviews acquired from diverse sources such as books, scientific portals, and journal articles. The reported findings indicate that ethnobotany significantly contributes to the identification and utilization of plants as primary resources for therapeutic products in diverse case studies. Utilizing local information derived from scientific methodologies can stimulate the generation of innovative ideas for constructing sustainable economic value in business. The incorporation of community knowledge has a significant impact on the advancement of ethnobotanical studies, which in turn facilitates the progress of research and technologies associated with bioprospecting.